Rising South Korea: A Minor Player or a Regional Power? - David Shim; Patrick Flamm (German Institute of Global and Area Studies (GIGA), 2012)
South Korea's rising status in regional and global affairs has received much attention in recent years. But in academic, media and policy debates South Korea is usually regarded as a mere middle power that, due to its geopolitical situation, has only limited leeway in its foreign policy. Accordingly, it must constantly maneuver between its larger neighbors: China, Japan and Russia. However, this perspective neglects the fact that the same geopolitical constraint also applies to other states in the region. No country can easily project its power over others. We use the concept of regional power as a template to discuss South Korea's rising stature in regional and global politics. We argue that Seoul seems quite capable of keeping up with other assumed regional powers. Hence, we not only provide a novel account of South Korea's foreign policy options but also go beyond current approaches by asking about the (undetermined) possibilities for Seoul's regional relations.
Keywords: 300; South Korea; security and foreign policy; middle power; regional power; regional order; East Asia; Außenpolitik; Südkorea; Geopolitik; Internationale Beziehungen; Ostasien